2021
DOI: 10.3390/su13179830
|View full text |Cite
|
Sign up to set email alerts
|

Primary School Physical Education at the Time of the COVID-19 Pandemic: Could Online Teaching Undermine Teachers’ Self-Efficacy and Work Engagement?

Abstract: This study aimed to evaluate whether primary school classroom teachers reported changes in physical education teaching self-efficacy (SE-PE) and work engagement (WE) during the first COVID-19 wave. A total of 622 classroom teachers filled in an online questionnaire on SE-PE and WE, referring to before and during the lockdown, and on perceived digital competence. While controlling for perceived digital competence, a mixed between-within Repeated Measures Multivariate Analysis of Covariance (RM-MANCOVA) was perf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 45 publications
3
12
2
Order By: Relevance
“…In line with the previous studies, male teachers' mean score of job satisfaction was still higher (M = 3.88, SD = 0.69) than female teachers' mean score (M = 3.79, SD = 0.68). However, the current results indicate a positive and insignificant correlation (r = 0.011, p > 0.01) between teachers' age and job satisfaction, while in the previous studies it was negative [5]. Teachers ≤ 15 years of age were still advantaged with job satisfaction (M = 3.89, SD = 0.62) compared to teachers > 15 years of age, and the correlation between teachers' experience and job satisfaction was unchanged, it was negative and insignificant (r = −0.002, p > 0.01).…”
Section: Teachers' Work Values Work Engagement and Job Satisfactioncontrasting
confidence: 93%
See 3 more Smart Citations
“…In line with the previous studies, male teachers' mean score of job satisfaction was still higher (M = 3.88, SD = 0.69) than female teachers' mean score (M = 3.79, SD = 0.68). However, the current results indicate a positive and insignificant correlation (r = 0.011, p > 0.01) between teachers' age and job satisfaction, while in the previous studies it was negative [5]. Teachers ≤ 15 years of age were still advantaged with job satisfaction (M = 3.89, SD = 0.62) compared to teachers > 15 years of age, and the correlation between teachers' experience and job satisfaction was unchanged, it was negative and insignificant (r = −0.002, p > 0.01).…”
Section: Teachers' Work Values Work Engagement and Job Satisfactioncontrasting
confidence: 93%
“…In this case, teachers' level of work engagement in their workplace is determined by their work values. The results are in line with other studies, in Italy for example [5], which demonstrated the effect of work values on work engagement, adding that teachers' work engagement had a significant decrease after the lockdown. The correlation between work values and work engagement was also high (r = 0.499, p < 0.01).…”
Section: The Effects Of Teachers' Work Values and Work Engagement On ...supporting
confidence: 92%
See 2 more Smart Citations
“…However, traditional teaching was often alternated with hybrid teaching, due to Covid infections forcing one or more pupils into quarantine periods. Teachers, students, and their families had to cope with a completely new situation ( 2 , 3 ), implementing new strategies, changing the processes of teaching-learning, communication, and emotional relationships with students ( 4 , 5 ). Primary school teachers faced many challenges when providing online and hybrid teaching, trying to quickly adapt their teaching to the contingent needs of distance or hybrid teaching.…”
Section: Introductionmentioning
confidence: 99%